Odnos Antona Mahniča do Sokola - Aleš Šafarič (Dileme, 2019)
The article deals with Anton Mahnič’s attitude towards the gymnastic organisation Sokol at the end of the 19th century based on an analysis of his articles. It also presents Mahnič’s views on topics that are closely related to the question of physical education and are the basis of his criticism of the Sokol movement as well as the responses of the environment to these first attacks on the views of the organisation. The article also explains Mahnič’s changing attitude towards exercise and sport in general and presents his role in the Catholic physical education organisation Orel.